2022
DOI: 10.3324/haematol.2022.281140
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of fetal microchimeric cells to maternal wound healing in sickle cell ulcers

Abstract: Leg ulcers are a major complication of sickle cell disease (SCD) that can cause severe complications. They are particularly challenging to treat and therapeutic innovation is needed. We previously showed that SCD ulcers display a delayed wound healing due to decreased angiogenesis. During pregnancy, fetal microchimeric cells (FMC) transferred to the mothers are recruited to maternal wounds and improve angiogenesis. After delivery, FMC persist in maternal bone marrow for decades. Here, we questioned whether fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…El Hoss et al have demonstrated that fetal haemoglobin, produced by fetal haemoglobin-containing cells (F-cells), decreases ineffective erythropoiesis 9 by playing an antiapoptotic role in terminal erythroid differentiation. In the present study, the authors demonstrated that fetal cells display features of hematopoietic progenitor cells by the high expression of genes associated with hematopoietic stem cells, such as Sca1 and Myc 5 .…”
Section: Fetal Microchimerism and Beyond: A New Player In Regenerativ...supporting
confidence: 52%
See 4 more Smart Citations
“…El Hoss et al have demonstrated that fetal haemoglobin, produced by fetal haemoglobin-containing cells (F-cells), decreases ineffective erythropoiesis 9 by playing an antiapoptotic role in terminal erythroid differentiation. In the present study, the authors demonstrated that fetal cells display features of hematopoietic progenitor cells by the high expression of genes associated with hematopoietic stem cells, such as Sca1 and Myc 5 .…”
Section: Fetal Microchimerism and Beyond: A New Player In Regenerativ...supporting
confidence: 52%
“…These fetal cells can differentiate into leukocytes and endothelial cells, thus contributing to the healing of the ulcers. This is not surprising since amniotic fluid stem cells can accelerate wound healing by enhancing reepithelialization and reducing scarring 5 . It has previously been shown, by some of the same authors, that the ccl2/ccr2 signalling is responsible for the recruitment of fetal cells in maternal wound healing 6 .…”
Section: Fetal Microchimerism and Beyond: A New Player In Regenerativ...mentioning
confidence: 99%
See 3 more Smart Citations